The influence of village funds on community empowerment in tourism villages - Fithriana, Noora; Eka, Fransiska; Sasmito, Cahyo (Universitas Islam Malang, 2023)
This study aims to measure how much influence village funds have on community empowerment in Pujon Kidul Tourism Village using quantitative methods. This study collected primary data from closed questionnaires which were distributed randomly to 100 respondents including village government, youth leaders and community leaders. This research questionnaire is valid and reliable while the results of this study have been tested. The results of this study indicate that the predictor size of the variation of the independent variable on the dependent variable is 0.528 and every time there is an addition to the independent variable, an addition of 0.768 will also be experienced by the dependent variable. With these results, the conclusion is that there is an influence of village funds on community empowerment which implies that village funds have a positive influence on community empowerment. This positive influence can occur due to the adequacy of village fund financing for community empowerment as a priority area in the Pujon Kidul Tourism Village. By disbursing village funds to tourism villages, in this case, village communities are empowered.